Posko Community Service Lecture 80 in Management Establishment and Development Qur’an Education Kindergarden - Suherdi; Ahmad; Nurfadillah.s; Nurul Ulmi; Putri Nabila; ReshiHadriyahrahmadana; Rikasari; Riska Yanti; Rismawati; Suci Syahrawani; Sulfiana (Makkareso: Riset Pengabdian Masyarakat, 2023)
Al-Qur'anic Education Kindergarten is one of them, implemented in a manner that is both informal and available under the governing law, about maintenance parks and Qur'anic education. Al-Qur'an Education Kindergarten is also beneficial for the growth of the child so that later efforts to eradicate blind reading of the Koran can be minimised. Al-Qur'an Education Kindergarten aims to provide training and learning to children starting at an early age by teaching an introduction to the Quran. In addition, Al-Qur'an Education Kindergarten teaches related Islamic religious sciences.